Expand: (x-1)^3

Given expression: (x – 1)3
Using the algebraic identity: (a – b)3 = a3 – b3 – 3ab(a – b)
(x – 1)3 = x3 – 13 – 3(x)(1)(x – 1)
= x3 – 1 – 3x(x – 1)
= x3 – 1 – 3x2 + 3x
Therefore, (x – 1)3 = x3 – 3x2 + 3x – 1.

Was this answer helpful?

 
   

0 (0)

(1)
(1)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question